Orbital free ab initio molecular dynamics simulation study of some static and dynamic properties of liquid noble metals - Bhuiyan, G.M.; Gonz´lez, L.E.; Gonz´lez, D.J. (Condensed Matter Physics, 2012)
Several static and dynamic properties of liquid Cu, Ag and Au at thermodynamic states near their respective melting points, have been evaluated by means of the orbital free ab-initio molecular dynamics simulation method. The calculated static structure shows good agreement with the available X-ray and neutron diffraction data. As for the dynamic properties, the calculated dynamic structure factors point to the existence of collective density excitations along with a positive dispersion for l-Cu and l-Ag. Several transport coefficients have been obtained which show a reasonable agreement with the available experimental data. Оцiнено деякi статичнi та динамiчнi властивостi рiдких Cu, Ag i Au при термодинамiчних умовах, близьких до їх точок плавлення, за допомогою методу безорбiтальної першопринципної молекулярної динамiки.
Розрахована статична структура добре узгоджується з наявними даними, отриманими з рентгенiвської i нейтронної дифракцiй. Щодо динамiчних властивостей, то розрахованi динамiчнi структурнi фактори вказують на iснування колективних збуджень густини поряд з позитивною дисперсiєю для l–Cu i l–Ag.
Отримано деякi коефiцiєнти переносу, якi прийнятно узгоджуються з наявними експериментальними даними.